2017
DOI: 10.1111/cen3.12394
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica spectrum disorders: Emerging therapies

Abstract: Neuromyelitis optica or neuromyelitis optica spectrum disorders (NMOSD) are autoimmune diseases associated with a disease-specific autoantibody directed against the water channel protein aquaporin-4. While almost all patients with NMOSD show a relapsing-remitting course, just 2% of patients present with a progressive course, suggesting that preventing acute attacks can lead to stable remission and avoid progression of the condition. Standard immunotherapy, immunosuppressive agents, and corticosteroids can prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disease of the central nervous system (CNS) that is characterized by inflammatory and demyelinating lesions in optic nerve, spinal cord brainstem and cerebrum, which can lead to progressive impairment of vision and motor functions [ 1 4 ]. The primary goal of NMOSD treatment is to reduce the risk of irreversible neurological impairment by preventing relapse and reducing the severity of attacks [ 5 , 6 ]. Recent research suggested that interleukin-6 (IL-6) has an important role in the immunopathogenesis of NMOSD [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disease of the central nervous system (CNS) that is characterized by inflammatory and demyelinating lesions in optic nerve, spinal cord brainstem and cerebrum, which can lead to progressive impairment of vision and motor functions [ 1 4 ]. The primary goal of NMOSD treatment is to reduce the risk of irreversible neurological impairment by preventing relapse and reducing the severity of attacks [ 5 , 6 ]. Recent research suggested that interleukin-6 (IL-6) has an important role in the immunopathogenesis of NMOSD [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phase I/II clinical trials were discontinued for various reasons. Sivelestat has already been approved in Japan and Korea for ARDS treatment [ 156 ].…”
Section: Emerging Therapeutic Approachesmentioning
confidence: 99%
“… 74 Although phase I/II clinical trials were discontinued for various reasons, a granulocyte-targeting therapy remains a promising therapeutic approach. 75 …”
Section: Prevention Of Relapsesmentioning
confidence: 99%